Herpetofauna Diversity from Khamgaon, district Buldhana (M.S.) Central India - Bawaskar Prakas S; Bawaskar Kiran S (International Journal of Life Sciences, 2016)
Preliminary checklist of Herpetofauna diversity from Khamgaon taluk, district Buldhana (M.S.) Central India at co-ordinate Latitude 20.6833, Longitude 76.5666. In present there is no report on Herpetofauna diversity from Khamgaon taluk, so the present study has been carried out during 2010-2015 in an alternatively days and nights herping. The study area covers such as Marshes, grass lands, rocky area, farm lands, scrub lands, forest, hilly area, villages and town. It was observed that 13 species found to be an abundant, 14 species were common, 12 species were uncommon, 9 species were occasional and 10 species were found to a rare. A general trend increased Herpetofauna population was observed in monsoon while comparatively less population of Herpetofauna observed during a winter to early monsoon.